ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Hikmah, An Wariyatul; Mulyono, Nono; Hidayat, Yusuf (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
The Independent Curriculum is a curriculum giving teachers the flexibility to determine learning media according to the students’ learning needs and interests. This study aims to find out the implementation of the Independent Curriculum and the factors that support the success in learning Islamic Religious Education in elementary school. The method used in this study is a qualitative under a case study approach. The results of the study show that the implementation of the Independent Curriculum in PAI education in grade 1 MI NU 03 Kebonagung is in the form of the students learn to know, recite, memorize the Alfatihah letter and its verse numbers, the students know the content of the Alfatihah letter, and practice in daily life. In addition, the implementation of the Independent Curriculum in PAI learning in grade 4 MI NU 03 Kebonagung in the form of the students are able to recite the letters of Allahab and Attakatsur correctly, the students are able to write the letters of Allahab correctly, the students are able to express opinions about the meaning of the letters of Attakatsur, and the students understand the content of the letter Alma'un and its practice in the real life. The supporting factors for the successful implementation of the Independent Curriculum in PAI learning at MI NU 03 Kebonagung include: the teachers' understanding of the implementation of the Independent Curriculum, classroom management, principal leadership, financing, facilities and infrastructure, and the students’ readiness.